American crisis leadership lessons from the Covid-19 pandemic - Cuomo, Andrew (New York Crown, 2020)
When COVID-19 besieged the United States, New York State emerged as the global "ground zero" for a deadly contagion that threatened the lives and livelihoods of millions. Quickly, Governor Andrew Cuomo provided the leadership to address the threat, becoming the standard-bearer of the organized response the country desperately needed. With infection rates spiking and more people dying every day, the systems and functions necessary to combat the pandemic in New York--and America--did not exist. So Cuomo undertook the impossible. He unified people to rise to the challenge and was relentless in his pursuit of scientific facts and data. He quelled fear while implementing an extraordinary plan for flattening the curve of infection. He and his team worked day and night to protect the people of New York, despite roadblocks presented by a president incapable of leadership and addicted to transactional politics.
Keywords: Covid 19